Structure of an immunoglobulin Fab fragment specific for triple-stranded DNA - Mol, C.D.; Muir, A.K.; Cygler, M.; Lee, J.S.; Anderson, W.F. (The Journal of biological chemistry, 1994)
Triple-stranded DNA of the form poly(Pyr).poly-(Pur).poly(Pyr) (where Pyr represents a pyrimidine, and Pur represents a purine) has become the subject of intense research because of its potential use in the control of gene expression and in the development of sequence-specific reagents for cleaving DNA. In a triplex of this type, the second pyrimidine strand is in a parallel orientation to the purine strand and forms Hoogsteen base pairs with it via the major groove. We describe here the three-dimensional crystal structure determination of the antigen-binding fragment (Fab) from the murine monoclonal antibody Jel 318. Jel 318 is specific for triple-stranded DNA, with a preference for the sequence poly[d(T.m5C)].poly[d(G.A)].poly[(d(m5C+.T)]. The structure has been solved by the molecular replacement method and refined by molecular dynamics to an R value of 0.20 at a resolution of 2.8 A. The crystals have cell dimensions that are very similar to those of the previously determined structure of Fab Kol, but the Fab fragments pack within the unit cell in a completely different manner. The protein is in an extended conformation, with an elbow angle of 154 degrees. The shape and electrostatic surface potential of the antibody combining site suggest a possible model for the recognition of triplex DNA in which residues of CDR-H2 (where CDR represents complementarity-determining region) make specific contact with the DNA bases in the minor groove of the triplex.